A logic model approach: understanding the impact of local Macmillan cancer information and support services in the UK (Journal of EAHIL, 2016)
Health information services are increasingly expected to demonstrate their impacts. One mechanism for doing so is to use a logic model. This article outlines the application of a logic model approach to the development and evaluation of local Macmillan cancer information and support services in the UK. It exemplifies the value of enabling service providers and other stakeholders to work together to agree the intended impacts of a service and how these will be measured. The logic model itself provides a clear graphic to illustrate how service activities lead to outputs, outcomes and impacts. This approach could be used more widely in health libraries and information services.